تقييم الأذى الزلزالي باستخدام منحنيات التضرر الاحتمالي للمباني البيتونية المسلحة ذات جمل إطارية مقاومة للعزوم - دبانة نبيل; منصور نزيه; دبول غنوة (Latakia University Journal -Engineering Sciences Series, 2018)
The damage to the buildings during earthquakes has demonstrated the need of seismic evaluation which is used to predict the probability of damage to the building. This paper describes the vulnerability assessment of four reinforced concrete buildings in Lattakia city using fragility curves. Fragility curves are used to describe the probability of damage being exceeded a particular damage state. For the development of fragility curves, guidelines given by HAZUS technical manual have been used. For the analysis, the RC buildings were modeled in SAP2000 v14.1, Non-linear static analysis procedure is used for the analysis of RC buildings. The pushover analysis is carried out as per the ATC40 guidelines. Capacity curve is generated as a result of pushover analysis. Results from pushover analysis are used for plotting fragility curves. The Fragility Curves are plotted considering Spectral Displacement as a ground motion parameter. Various ‘damages states’ are used to describe the damage level of the building given in HAZUS technical manual. Finally, using constructed fragility curves the spectral displacement values that satisfy the ‘slight’, ‘moderate’, ‘extensive’, ‘complete’ performance level requirements were estimated. The fragility curves developed from the analysis were used to study the seismic performance of building models تقييم الأذى الزلزالي باستخدام منحنيات التضرر الاحتمالي للمباني البيتونية المسلحة ذات جمل إطارية مقاومة للعزوم يُعد تقييم التضرر الزلزالي الاحتمالي للجمل الانشائية من الطرائق الرياضية الاحصائية التي تبين احتمال وصول منشأ لمستوى ما من الأذى الزلزالي وخلق نظرة مستقبلية لتقييم التضرر الزلزالي لأي مبنى قائم وذلك باستخدام توابع توزيع تراكمي تعبر عن احتمال تعرض المنشآت للأذى كتابع للبارامترات الزلزالية (التسارع الزلزالي أو التسارع الطيفي أو الانتقال الطيفي), دُرس في البحث أربعة أبنية قائمة مختلفة تقع في نفس المنطقة الزلزالية وهي منطقة اللاذقية, حيث تم تقييم أداء هذه المباني باعتماد طريقة االتحليل الستاتيكي اللاخطي وفق اشتراطات ATC40 باستخدام برنامج Sap2000(ver14), وعرفت عتبات التضررDamage في البحث وفق ما ورد في اشتراطات HAZUS-MR5 وفق أربعة عتبات تضرر خفيف ومتوسط وشامل وتام (Slight_Moderate_Extensive_Complete), تم ايجاد منحنيات التضرر الاحتمالي للمباني الأربعة وذلك لحالات مستويات التضرر الأربعة, وتبين النتائج تقييم لكفاءة الأبنية من خلال قراءة لاحتمال التضرر الزلزالي للمباني المدروسة بالنسبة للانتقال الطيفي والتسارع الطيفي تحت تأثير الشدة الزلزالية الموافقة لمنطقة البناء.